Revised trauma score as a predictor of in-hospital mortality in polytrauma patients treated at the Hospital Belén in Trujillo, Peru - Macedo Pinedo, Christian (2023)
Objective: To determine whether the revised trauma score is a predictor of in-hospital mortality in polytrauma patients treated at Hospital Belén de Trujillo. Material and methods: An observational, analytical, retrospective, cross-sectional study of diagnostic tests was conducted, identifying patients who were admitted for polytrauma and were hospitalized in the Department of General Surgery during the period from January 2017 to December 2021; mortality was assessed in a sample of 100 patients. Results: Mean age was 47.18 ± 20.40 vs 41.13 ± 18.37 in those who died and survived; 55% and 63.33% of the deceased and survivors were male in the study groups. Coagulopathy, metabolic acidosis and SIRS were associated with mortality. A proportion of 72.50% and 3.33% STR < 6 was observed in polytrauma patients who died and survived (p = 0.001); sensitivity: 73% CI 95% [59% - 86%], specificity: 97% CI 95% [92% - 100%], positive predictive value: 94% CI 95% [85% - 100%] and negative predictive value: 84% CI 95% [75% - 93%]. The area under the curve was 96.50% in predicting mortality by RTS in polytrauma patients. Conclusion: The revised trauma score is a good predictor of mortality in polytrauma patients.